Canva-Based e-Comic Development on Pancasila Education Subjects for Grade IV Elementary School - Deva Septia Dwi Putri; Tio Gusti Satria; Lucy Asri Purwasi (EDUJAVARE: International Journal of Educational Research, 2026)
Along with the development of the times, the curriculum in Indonesia continues to undergo changes to adapt to global needs. This research aims to develop a Canva-based e-comic media design for the Pancasila Education subject for grade IV elementary school. Testing the validity, practicality, and effectiveness of Canva-based e-comic media in the Pancasila Education subject for grade IV of SD Negeri 49 Lubuklinggau. This form of investigation is categorized as Research and Development utilizing the ADDIE framework for development. The participants involved in this examination were fourth graders from SD Negeri 49 Lubuklinggau. Techniques for gathering data involved the use of questionnaires and assessments. According to the findings from the validity evaluation of the Canva-based e-comic media employing Aiken's V, the score given by the language validator was 0,94 the score from the media validator was 0,88 and the score from the material validator was 0,94. The evaluation of the practicality assessments conducted by both teachers and students indicated that the e-comic media designed through Canva for the Pancasila Education course achieved a high practicality rating, receiving an average score of 92% Furthermore, the effectiveness evaluation resulted in an N-Gain score averaging 0,7 which falls within the high category. From the findings of this study, it can be determined that the Canva-based e-comic media for the Pancasila Education course for fourth-grade elementary students is demonstrated to be valid, practical, and effective. Thus, it is deemed appropriate for implementation in the Pancasila Education subject for fourth grade at SD Negeri 49 Lubuklinggau.